Plasma microRNAs expression profile in female workers occupationally exposed to mercury - Ding, Enmin; Zhao, Qiuni; Bai, Ying; Xu, Ming; Pan, Liping; Liu, Qingdong; Wang, Bosheng; Song, Xianping; Wang, Jun; Chen, Lin; Zhu, Baoli (Journal of Thoracic Disease, 2016)
Background: Circulating microRNAs (miRNAs) have attracted interests as non-invasive biomarkers of physiological and pathological conditions. Several studies have examined the potential effects of mercury exposure on miRNAs expression profiles of general population environmentally exposed to mercury. The objective is to identify mercury-related miRNAs of female workers occupationally exposed to mercury. Methods: In this case-control study, we used a microarray assay to detect the miRNA expression profiles in pooled plasma samples between (I) chronic mercury poisoning group; (II) mercury absorbing group and (III) control group in the discovery stage. Each group has ten individuals. In addition, we conducted a validation of eight candidate miRNAs in the same 30 workers by quantitative real-time PCR. Results: In the discovery stage, eight miRNAs were conformed following our selection criteria. In the validation stage, RT-PCR confirmed up-regulation of miR-92a and miR-486 in the mercury poisoned group (P